Pendampingan Pengabdian Kepada Masyarakat Bagi Pengrajin Tenun Troso di Kabupaten Jepara - Sulistyowati Sulistyowati; Mamik Indaryani; Kertati Sumekar; Sri Mulyani; Budi Gunawan; Fajar Nugraha (Empowerment: Jurnal Pengabdian Masyarakat, 2022)
Empowerment of SMEs in the midst of globalization and high competition makes SMEs must be able to adapt to global challenges, such as ho to increasing product innovation, both in the form of goods and services, how to develop human resources and technology, and how to expanding networking in marketing. One of the SMEs’ creative industry is Troso Village, Mlonggo District, in Jepara Regency, Central Java. A village which almost all people there are in Weaving Industri., and is known as Troso Weaving. Weaving is also a creative industry, because it is based on culture. In line with government policies that are focused on developing creative industries based on local culture and uniqueness. This empowerment trainings are also serves as a laboratory and an education class for selected students to be able to implement the Merdeka Belajar Kampus Merdeka (MBKM) system. This Community Service is a form of Triple Helix, a form which connected between Universities, government and society. This activity includes the form of training that is presented through presentations, simulations and mentoring.